Ensuring accuracy of contour milling on CNC machines - Yury Petrakov; Yan Romanov (Mechanics and Advanced Technologies, 2023)
Contour milling is characterized by quasi-stationary, which leads to the occurrence of a machining error caused by elastic deflections of the machining system. Moreover, such an error cannot be eliminated by sub-adjusting the control program "for size", since it not is constant and changes along the contour in a wide range. To ensure the accuracy of contour milling, a new method of combined control is proposed, which uses a posteriori information of machine verification measurements of the machined surface and a priori information of modeling the material removal process. In case of single manufacturing, the allowance on the last pass is divided into two parts, and after machining the first part, verifications are performed, then modeling and machining of the second half according to the corrected control program. In mass manufacturing, verifications are performed on the first part, and all subsequent ones are machined according to the adjusted control program. To obtain the necessary a posteriori information, the technology of machine verifications on CNC-machine with a three-coordinate probe according to standard control programs is proposed, and it is enough to perform two measurements or one, in the presence of surfaces inclined to the coordinate axes of the contour. A computer program was created, the core of which is a mathematical model of the process, which reproduces the structural diagram of the machining system closed behind two elastic deflections. The primary control file is loaded in G-codes with measurement data, and as a result of the process simulation, a new control file for the CNC-machine tool is formed, which eliminates the error from elastic deflections of machining system. Preliminary tests showed the possibility of increasing the accuracy of contour machining by more than 3 times.